2020
DOI: 10.1257/pol.20180352
|View full text |Cite
|
Sign up to set email alerts
|

Do Human Capital Decisions Respond to the Returns to Education? Evidence from DACA

Abstract: This paper studies human capital responses to the availability of the Deferred Action for Childhood Arrivals (DACA) program, which provides temporary work authorization and deferral from deportation for undocumented, high-school-educated youth. We use a sample of young adults that migrated to the United States as children to implement a difference-in-difference design that compares noncitizen immigrants (“eligible”) to citizen immigrants (“ineligible”) over time. We find that DACA significantly increased high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 60 publications
(55 reference statements)
9
45
1
Order By: Relevance
“…I didn't understand the limitations of it at that point, but I understood that it would allow me to at least pay for my education, and to at least see that dream through." These testimonies were consistent with a study from the National Bureau of Economic Research which found that DACA "significantly increased high school attendance and high school graduation rates, reducing the citizennoncitizen gap in graduation by 40%" (Kuka et al, 2018).…”
Section: The Impact Of Dacasupporting
confidence: 87%
“…I didn't understand the limitations of it at that point, but I understood that it would allow me to at least pay for my education, and to at least see that dream through." These testimonies were consistent with a study from the National Bureau of Economic Research which found that DACA "significantly increased high school attendance and high school graduation rates, reducing the citizennoncitizen gap in graduation by 40%" (Kuka et al, 2018).…”
Section: The Impact Of Dacasupporting
confidence: 87%
“…A case in point is the Deferred Action for Childhood Arrivals (DACA) with its positive immigration stance. The program is credited for significant improvements in high school attendance and graduation rates among DACA‐eligible non‐citizen immigrants (Kuka, Shenhav, & Shih, 2020). Amuedo‐Dorantes and Antman (2017), however, qualify that higher‐educated DACA‐eligible immigrants tend to prefer employment alternatives instead of higher educational pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…Their samples were 60% to 66% female, compared to 53% in each of two larger data sets (USCIS, 2016;Zong et al, 2017). Their samples revealed that 70% to 71% of respondents had attained "some college," compared to 37% in the Migration Policy Institute (MPI) study and c. 31% in a National Bureau of Economic Research study (Kuka et al, 2018). This tilting of the sample toward educated females may have led to more positive results on education than would have resulted from a more representative sample.…”
Section: National Levelmentioning
confidence: 99%